Naproxen kinetics in synovial fluid of patients with osteoarthritis. - Bruno, R (1988)
1. The kinetics of naproxen in synovial fluid were studied in 407 osteoarthritic outpatients with knee effusion requiring aspiration, following a single 1100 mg oral dose of naproxen sodium. 2. The drug concentration-time profiles were described by a biexponential function. Naproxen entered synovial fluid rapidly, reaching a maximum concentration of 36 mg l-1 (Cmax) at 7.5 h. The first order input rate constant (kOs) was 0.41 +/- 0.15 h-1 with a lag time (tlag) of 0.24 +/- 0.36 h. 3. Elimination from the fluid was slow (t1/2 = 31 +/- 12 h) and appreciable drug concentrations were still measurable (27 mg l-1) after 24 h. 4. During once daily dosing of naproxen sodium, naproxen should accumulate in synovial fluid, a steady-state being achieved within a week of treatment. The predicted accumulation ratio based on trough concentration was 2.4.